2022
DOI: 10.1007/s41109-022-00477-9
|View full text |Cite
|
Sign up to set email alerts
|

Map equation centrality: community-aware centrality based on the map equation

Abstract: To measure node importance, network scientists employ centrality scores that typically take a microscopic or macroscopic perspective, relying on node features or global network structure. However, traditional centrality measures such as degree centrality, betweenness centrality, or PageRank neglect the community structure found in real-world networks. To study node importance based on network flows from a mesoscopic perspective, we analytically derive a community-aware information-theoretic centrality score ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
(52 reference statements)
0
5
0
1
Order By: Relevance
“…Bertolero and colleagues [50] addressed a similar question by studying a large variety of networks and found that diverse clubs (nodes with diversely distributed links), rather than rich clubs (interconnected high-degree nodes), play a more prominent role in the integration of information in networks. Furthermore, studies in network science have advocated for considering community-aware centrality measures [75]. Taken together, these findings suggest that degree centrality may not be an appropriate measure for functional networks.…”
Section: Discussionmentioning
confidence: 99%
“…Bertolero and colleagues [50] addressed a similar question by studying a large variety of networks and found that diverse clubs (nodes with diversely distributed links), rather than rich clubs (interconnected high-degree nodes), play a more prominent role in the integration of information in networks. Furthermore, studies in network science have advocated for considering community-aware centrality measures [75]. Taken together, these findings suggest that degree centrality may not be an appropriate measure for functional networks.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular approach to explore influential nodes in complex networks has been to used centrality measures [15][16][17][18][19][20][21] . From the perspective of global and local information, typical methods based on local information include methods considering the degree centrality (DC) 22 and methods considering the eigenvector centrality (EC) 23 .…”
Section: Exploring Influential Nodes Using Global and Local Informationmentioning
confidence: 99%
“…One can also consider multidimensional measures simultaneously combining local and global information [11,12]. More recent works exploit the network's community structure to identify influential nodes [13][14][15][16][17][18][19][20]. They show that the community structure is a crucial factor in effectively quantifying the node's influence [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The community structure of a network affects its underlying dynamics [29,30]. Moreover, ongoing research emphasizes the benefits of the community structure as a basis for identifying influential nodes [13][14][15][16][17][18][19][20]. The proposed ranking strategy exploits this precious information.…”
Section: Introductionmentioning
confidence: 99%